A Prospective Randomized Study on Two Dose Fractionation Regimens of High-Dose-Rate Brachytherapy for Carcinoma of the Uterine Cervix: Comparison of Efficacies and Toxicities Between Two Regimens - Nam, Taek Keun (The Korean Academy of Medical Sciences, 2004)
To evaluate the toxicities and efficacies of two fractionation regimens of high-dose-rate brachytherapy in uterine cervical cancer, patients were stratified by stage Ib-IIa versus IIb-IVa, and randomly assigned to receive 3 Gy fractions (group A) or 5 Gy fractions (group B). External radiotherapy was performed using a 10 MV radiography with a daily 1.8 Gy up to 30.6 Gy to the whole pelvis, and then with a midline shield up to 45.0 Gy. Brachytherapy was performed with 3 Gy × 10 times or 5 Gy × 5 times, and this was followed by booster brachytherapy of a smaller fraction to the residual tumor. Between August 1999 to July 2000, 46 patients were eligible. Median follow-up period was 42 months (5-49). The range of age was 37-83 yr (median, 58). The three-year disease-specific survival rates of group A (n=23) and B (n=23) were 90.5%, 84.9%, respectively (p=0.64). The three-year pelvic control rates of group A and B were 90.0% and 90.9%, respectively (p=0.92). The incidences of late complications of the rectum or bladder of grade 2 or greater in groups A and B were 23.8% and 9.1%, respectively (p=0.24). Our study showed that the results of two regimens were comparable. Fractionation regimen using 5 Gy fractions seems to be safe and effective, and offers shorter treatment duration.